Effects of Y and Hf addition on soft magnetic property and ductility improvement of Fe–6.9 wt% Si alloy - Guojun Cai; Yanru Huang; Yongquan Qing; R.D.K. Misra (Journal of Materials Research and Technology)
Fe–6.9 wt% Si alloy is superior to conventional electrical steels containing 3 wt%Si in terms of soft magnetic performance at high frequencies but its lack of ductility resulting in large restriction on workability and shaping. In present investigation, an excellent ductile behavior was observed in the Fe–6.9 wt% Si alloy containing Y and Hf, together with high magnetic induction B8 of 1.385 T and B50 of 1.661 T, as well as low core loss P10/1000 of 32.168 W/kg. Smaller-sized Y2O3 oxides were diffusely distributed in 6.9Si–0.03Y alloy, while the irregular larger-sized Y2Hf2O7 oxides were distribute randomly in grains and at grain boundaries of 6.9Si–0.03Y–0.2Hf alloy. Y-Hf-containing oxides caused the preferential nucleation advantage of λ oriented grains in the nucleation process and hindered the development of γ-fiber recrystallization textures during final annealing, leading to an excellent soft magnetic property of 6.9Si–0.03Y–0.2Hf alloy. Benefiting from the suppression of brittle ordered phases and the change of dislocation configuration, the fracture strain of alloy increased from 6.7 % to 9.0 % in 6.9Si–0.03Y sheet and showed an excellent ductility value of 11.4 % duo to Hf addition. Y and Hf complex oxides doped in alloy provided an effective approach for improving the ductility without deterioration of soft magnetic property of high silicon steels.